2021
DOI: 10.3390/ijerph182211909
|View full text |Cite
|
Sign up to set email alerts
|

Key Parameters Affecting Kick Start Performance in Competitive Swimming

Abstract: The study aims to determine the contribution of kinematic parameters to time to 5 m without underwater undulating and kicking. Eighteen male competitive swimmers started from three weighted positions and set the kick plate to positions 1–5. We used SwimPro cameras and the Dartfish© software. In the on-block phase, we found significant correlations (p < 0.01) between the front ankle angle and block time. The correlations between start phases were statistically significant (p < 0.01) between block time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…As the back plate has become more widely implemented and used during competitions, researchers have aimed to expose the importance of lower limb positioning over the starting platform (including the distance between the feet [ 13 ]) as well as the impact of the lower limb joint angles on the swimming start performance [ 14 ]. Several studies have hypothesized that the starting performance could be affected by only adjusting the back plate [ 15 , 16 , 17 ]; others have analyzed back plate displacement combined with different initial body positions [ 14 , 17 , 18 , 19 ]. However, a few of the available studies were based on block settings incompatible with official standards and included multiple factors acting on the measured output or did not consider sex-specific differences.…”
Section: Introductionmentioning
confidence: 99%
“…As the back plate has become more widely implemented and used during competitions, researchers have aimed to expose the importance of lower limb positioning over the starting platform (including the distance between the feet [ 13 ]) as well as the impact of the lower limb joint angles on the swimming start performance [ 14 ]. Several studies have hypothesized that the starting performance could be affected by only adjusting the back plate [ 15 , 16 , 17 ]; others have analyzed back plate displacement combined with different initial body positions [ 14 , 17 , 18 , 19 ]. However, a few of the available studies were based on block settings incompatible with official standards and included multiple factors acting on the measured output or did not consider sex-specific differences.…”
Section: Introductionmentioning
confidence: 99%
“…Three positions were monitored—front, neutral, and back. In most studies, shorter times were measured at 5 m, 7.5 m, and 15 m, respectively, at neutral-weighted or rear-weighted positions [ 6 , 7 , 8 , 9 , 10 ]. In the study by Burkhardt et al [ 11 ], the positioning of the lower limbs in the base position on the starting block did not show differences in the base position used between the stronger lower limb on the front edge or on the backrest.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Silveira et al [ 12 ], they found that after the kick-off from the start block, kick start and its modification showed that the key parameter was the flight length at the 5 m take-off distance. In a study by Matúš et al [ 8 ], start reaction, take-off angle, and time to 2 m distance were shown to be the key parameters in the 5 m distance start. When looking for key parameters at a 15 m distance in the study by Tor et al [ 13 ], length and time of flight were not among the key parameters affecting take-off performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the swimming styles (e.g., butterfly, backstroke, breaststroke, and front-crawl stroke), the start has evolved over time, the main ones being grab and track starts. Other ones (e.g., swing, handle, rear-weighted track, and front-weighted starts) have been conceived as variations of these two [6,7,8,9]. Investigations on swimming start have been developed based on different concerns, mainly to understand the kinematic and kinetic variables of the foregoing start styles [6,9,10,11].…”
mentioning
confidence: 99%
“…Although there is widespread recognition that swimming start unfolds by performing sequential components (e.g., phases), there has also been some distinction as to what they are and how they occur [21]. For example, while Maglischo [5] proposes that it involves preparatory position, pull, block impulsion, flight, entry, and slide, Matúš et al [8] suggest the phases of block, flight, and underwater.…”
mentioning
confidence: 99%